Transitioning into independent adult life: a phenomenological study of teenagers at a shelter home - Mohd munir, Nur Syuhada; Rais, Haniza (UPM Press, 2022)
Introduction: Studies on adolescents ageing out of shelter homes in Malaysia were scarce. This research aimed to explore the phenomenological experiences of the teenagers in their preparation to transition out from the shelter home upon reaching the age of 18 years towards the independent living phase. Method: This qualitative research employed a purposive sampling design that used focus group discussion as the main source for data collection. Thematic analysis was selected for the analysis of data to generate themes and sub-themes gathered from significant phrases shared from the participant’s responses in the group discussion. Five participants who met the criteria of inclusion were recruited for the focus group discussion. Results: The findings presented the challenges faced by the participants in preparing for their journey toward independent living. Among the issues shared were relationships, lacking skills and competencies, and mixed feelings faced by the participants as part of the overall concerns in the transition process. Conclusion: The findings of this research will hopefully shed light on the administration of shelter home institutions and policymakers for improvement of the services, facilities, and interventions for teenagers in helping them transition through emerging adulthood towards independent living.